Termodecomposiçao da celulose microcristalina e de seus derivados puros e contendo cátions cádmio II adsorvidos - Chahud, Marisa [UNESP]; Ionashiro, Massao [UNESP]; Moreira, José Celso [UNESP]; Campos, Joaquim Theodoro De Souza [UNESP] (My University, 1996)
We have studied the thermal decomposition of the microcrystalline cellulose and some of its derivative such as pure carboxymethylcellulose (CMCH), phosphate cellulose (FOSCEL) and oxycellulose (OXICEL) and also these same derivatives containing adsorbed cadmium cations. We have used the TG,DTG tecniques in order to determine the quantity of retained cadmium II cations on the surface of these adsorbents.
Thermal decomposition of microcrystalline cellulose and its pure and containing adsorbed cadmium cations derivatives
Keywords: Cadmium II adsorption; Cellulose and modified cellulose; Thermal decomposition